A practical approach to assess inhalation toxicity of metal oxide nanoparticles in vitro. Issue 2 (28th September 2017) - Dankers, Anita C. A.; Kuper, C. Frieke; Boumeester, Anja J.; Fabriek, Babs O.; Kooter, Ingeborg M.; Gröllers‐Mulderij, Mariska; Tromp, Peter; Nelissen, Inge; Zondervan‐Van Den Beuken, Esther K.; Vandebriel, Rob J.
Abstract: Exposure of humans to metal oxide nanoparticles (NPs) occurs mainly via air, and inhaled metal oxide NPs may generate inflammation. The aim of this study was to investigate the proinflammatory potential of six metal oxide NPs (CeO2, Mn2 O3, CuO, ZnO, Co3 O4 and WO3 ; 27–108 μg ml −1 ) using human primary 3‐dimensional airway epithelium (MucilAir™) and dendritic cell (DC) models. Metal oxide NPs were mainly aggregated/agglomerated in the cell media, as determined by dynamic light scattering, scanning electron microscopy and differential centrifugal sedimentation. WO3 and ZnO were highly soluble, both with and without respiratory mucus. Proinflammatory signalling by the epithelium was evaluated after a 24 hour exposure by increased interleukin‐6 and ‐8 and monocyte chemoattractant protein 1 cytokine release, which occurred only for CuO. Moreover, maturation of immature human DCs, which play a key role in the lung immune system, were evaluated by expression of surface markers HLA‐DR, CD80, CD83 and CD86 after a 48 hour exposure. Only Mn2 O3 consistently upregulated DC maturation markers. Furthermore, by addition of medium from metal oxide NP‐exposed 3‐dimensional airway cultures to metal oxide NP‐exposed DC cultures, the interplay between lung epithelium and DCs was studied. Such an interplay was again only observed for Mn2 O3 and in one of five DC donors. Our results show that, even when using dosages that represent very high in vivo exposure levels, up to 27 hours of constant human airway exposure, metal oxide NPs cause minimal proinflammatory effects and that epithelial cells not necessarily interfere with DC maturation upon metal oxide NP exposure. The present approach exemplifies a relevant translation towards human safety assessment. Abstract : The proinflammatory potential of metal oxide NPs CeO2, Mn2 O3, CuO, ZnO, Co3 O4 and WO3 was studied in human primary 3D airway epithelium and dendritic cells (DC) models. WO3 and ZnO were highly soluble, with and without respiratory mucus. Only CuO increased interleukin‐6 and ‐8, and monocyte chemoattractant protein 1. Only Mn2 O3 upregulated DC maturation markers. Addition of medium from Mn2 O3 ‐exposed 3D epithelium to Mn2 O3 ‐exposed DCs further increased DC maturation in one of five DC donors, at dosages representing up to 27 hours of human airway exposure.